Allusive and Elusive: Allusion and the Elihu Speeches of Job 32-37 - Smith, Cooper (Biblical Interpretation Series, 2022)
Elihu is among the most diversely evaluated characters in the Hebrew Bible. Attending to the inner-Joban allusions in the Elihu speeches (Job 32-37) provides both an explanation and appreciation for this diversity. After carefully defining allusion, this work identifies and interprets twenty-three allusions in Job 32-37 that refer to Job 1-31 in order to understand both their individual significance in the Elihu speeches and their collective significance as a compositional feature of the unit. This allusiveness is shown to both invite and explain the varied assessments of Elihu's merits in the history of interpretation.